THE EFFECT OF REAL MEDIA ON THE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT OF THE EIGHTH YEAR STUDENTS OF SMP SWASTA DEWANTARA PUTRA SEBERTUNG AT ACADEMIC YEAR 2018/2019 - Efrini Panjaitan M.Hum (STKIP Budidaya Binjai, 2019)
The study deals with an experimental research design which seeks for the effect of real media on students’ ability in writing procedure text. The problems that had been identified by the writer are including many of junior high school students have difficulties in understanding the genres of text, they still get lack of vocabularies which makes the students difficult to compose any kinds of text, the procedural texts seem hard for students to comprehend without any practical media, the written language is more complicated than spoken one, and teacher does not have very effective strategy to overcome the students’ inability in learning procedural text. 70 students at the eighth year students at SMP Swasta Dewantara Putra Sebertung in academic year of 2018/2019 are taken as the subject of the study. Multiple choices are used to obtain the data on the variable. The final data then is analyzed by using technique of t-test analysis. The result shows that coefficient of tcounted (3.37) was greater than the ttable coefficient (1.66757). This means that there is the effect of real media on students’ ability in writing procedure text of the 2018/2019 eighth year students of SMP Swasta Dewantara Putra Sebertung. Therefore, the hypothesis of the study is accepted.